2011
DOI: 10.1038/eye.2011.256
|View full text |Cite
|
Sign up to set email alerts
|

Can genetic risk information for age-related macular degeneration influence motivation to stop smoking? A pilot study

Abstract: Aims Smoking can increase the risk of macular degeneration and this is more than additive if a person also has a genetic risk. The purpose of this study was to examine whether knowledge of genetic risk for age-related macular degeneration (AMD) could influence motivation to quit smoking. Methods A questionnaire-based study of hypothetical case scenarios given to 49 smokers without AMD. Participants were randomly allocated to a generic risk, high genetic risk, or low genetic risk of developing AMD scenario. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
(43 reference statements)
1
10
0
2
Order By: Relevance
“…Candidate SNPs from both CFH and ARMS2 have consistently shown stronger associations with both exudative AMD and GA than with signs of early AMD. 15,1016,1822,4951,5367 Our results are consistent with cross-sectional findings from the Blue Mountains Eye Study, the Rotterdam Study and the ALIENOR study where persons who were homozygous for the CFH variant had increased odds ranging from 1.2 to 2.4 for early AMD compared to no AMD. 54,55,64 In addition, in the Rotterdam Study, the association became stronger with increasing severity of early AMD.…”
Section: Commentsupporting
confidence: 88%
See 1 more Smart Citation
“…Candidate SNPs from both CFH and ARMS2 have consistently shown stronger associations with both exudative AMD and GA than with signs of early AMD. 15,1016,1822,4951,5367 Our results are consistent with cross-sectional findings from the Blue Mountains Eye Study, the Rotterdam Study and the ALIENOR study where persons who were homozygous for the CFH variant had increased odds ranging from 1.2 to 2.4 for early AMD compared to no AMD. 54,55,64 In addition, in the Rotterdam Study, the association became stronger with increasing severity of early AMD.…”
Section: Commentsupporting
confidence: 88%
“…For example, data from a pilot study showed that smokers reported they would be more likely to quit smoking if told they were at high genetic risk of developing late AMD. 51 However, in the BDES, smoking status has not proven to be a risk factor for the cumulative incidence of late AMD, 52 and to date, it has not been demonstrated that interventions to alter behaviors (eg, change in diet, smoking cessation) affect the incidence of late AMD.…”
Section: Commentmentioning
confidence: 99%
“…This is even more relevant in smoking subjects, as a genetic high-risk profile might influence their motivation to quit smoking [106]. …”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 A pilot study in 49 smokers demonstrated that people given high genetic risk information were more likely to quit smoking than generic or low genetic risk groups. 18 …”
mentioning
confidence: 99%